Decolonizing the Mind: Historical Perspectives in a New Era - lasaiba, Mohammad Amin (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2022)
This research explores the decolonization of the mind from a historical perspective in the new era through a literature review method. Decolonizing the mind attempts to dismantle colonial legacies that still influence the postcolonial era's structure of knowledge, education, and social consciousness. By reviewing relevant academic literature, this research identifies how colonial discourses still dominate and how postcolonial theories attempt to challenge dominant Eurocentric narratives. The results show that despite the formal end of colonialism, many educational institutions and intellectual discourses still operate within a framework that marginalizes non-Western perspectives. This research also highlights the importance of epistemic inclusion and recognition of local knowledge as essential steps in decolonizing the mind. In addition, critiques of existing decolonization approaches are also discussed, particularly about the effectiveness of their implementation in creating real structural change. This research provides significant theoretical contributions and practical insights into how decolonization principles can be applied in various contexts to achieve sustainable transformation in the distribution of knowledge and power